An assessment of different beekeeping practices in South Africa based on their needs (bee forage use), services (pollination services) and threats (hive theft and vandalism) - Masehela, Tlou Samuel (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhDAgric)--Stellenbosch University, 2017.